A Phosphorus Bisylide: Exploring a New Class of Superbases with Two Interacting Carbon Atoms as Basicity Centers. Issue 11 (23rd February 2017) - Kögel, Julius F.; Margetić, Davor; Xie, Xiulan; Finger, Lars H.; Sundermeyer, Jörg
Abstract: Herein we present the first superbaseMHPN with two interacting P‐ylide entities. Unlike classical proton sponges, this novel compound class has carbon atoms as basicity centers which are forced into close proximity by a naphthalene scaffold. The bisylide exhibits an experimental p K BH + value of 33.3±0.2 on the MeCN scale and a calculated gas‐phase proton affinity of 277.9 kcal mol −1 (M062X/6‐311+G**//M062X/6‐31G*+ZPVE method) exceeding that of the corresponding monoylide by nearly 15 kcal mol −1 . The origin of the unexpectedly high basicity of the new bisylide was investigated by NMR spectroscopic methods, single‐crystal X‐ray diffraction as well as theoretical calculations and can be partly attributed to the rapid exchange of the "acidic" proton between the two basic carbon atoms after protonation. Abstract : Ping‐pong with protons : The first superbase with two interacting P‐ylide entities lets a proton bounce between two carbon atoms and exhibits a remarkable proton affinity with an experimental p K BH + value of 33.3±0.2 on the MeCN scale. The high basicity arises from the rapid exchange of the "acidic" proton between the two basic carbon atoms after protonation.